In vitro biological control of Pyrrhoderma noxium using volatile compounds produced by termite gut-associated streptomycetes - Adra, Cherrihan; Panchalingam, Harrchun; Foster, Keith; Tomlin, Russell; Hayes, R. Andrew; Kurtböke, D. İpek (Frontiers in Plant Science, 2024)
Introduction Pyrrhoderma noxium is a plant pathogen that causes economic losses in agricultural and forestry industries, including significant destruction to amenity trees within the city of Brisbane in Australia. Use of chemical control agents are restricted in public areas, there is therefore an urgent need to investigate biological control approaches. Members of the phylum Actinomycetota, commonly known as actinomycetes, are known for their industrially important secondary metabolites including antifungal agents. They have proven to be ideal candidates to produce environmentally friendly compounds including the volatile organic compounds (VOCs) which can be used as biofumigants. Methods Different Streptomyces species (n=15) previously isolated from the guts of termites and stored in the University of the Sunshine Coast’sMicrobial Library were tested for their antifungal VOCs against Pyrrhoderma noxium. Results Fourteen of them were found to display inhibition (39.39-100%) to the mycelial development of the pathogen. Strongest antifungal activity displaying isolates USC-592, USC-595, USC-6910 and USC-6928 against the pathogen were selected for further investigations. Their VOCs were also found to have plant growth promotional activity observed for Arabidopsis thaliana with an increase of root length (22-36%) and shoot length (26-57%). The chlorophyll content of the test plant had a slight increase of 11.8% as well. Identified VOCs included geosmin, 2-methylisoborneol, 2-methylbutyrate, methylene cyclopentane, β-pinene, dimethyl disulfide, ethyl isovalerate, methoxyphenyl-oxime and α-pinene. Additionally, all 15 Streptomyces isolates were found to produce siderophores and indole acetic acid as well as the enzyme chitinase which is known to break down the fungal cell wall. Discussion Findings indicate that termite gut-associated streptomycetes might be used to control Pyrrhoderma noxium by utilizing their wide range of inhibitory mechanisms.